Herd duration, size, and age composition in relation to British pedigree cattle breeding: with particular reference to the Ayrshire and Jersey breeds - El-Itriby, Abbas Ahmed (The University of Edinburgh, 1945)
The investigations reported in the following pages were undertaken with the object of adding to our knowledge of the populations of British pedigree cattle Until a reasonably complete account has been given of the structure, organization and biology of these populations, it will be difficult to make a just appraisal of present methods of breeding better livestock, or to design efficient measures for improving the rate of progress. As a result of recent developments in the field of population genetics, the possibility of guiding the evolution of domestic animals has been greatly extended, and it is hoped that the data now presented will prove useful in exploiting this opportunity.

Falling naturally, as they do, into four groups, the problems studied are described in four separate but related accounts. These deal with (a) the ages of cows and bulls; (b) the duration of herds; (c) the size of herds; and (d) the relation between herd size, milk recording and tuberculin testing. The account of herd size, which was enlarged by data provided by Dr. H. P. Donald, has already been published in the Journal of Agricultural Science.